(untitled) (Medical Forum Monthly, 2023)
Objective: To review existing research on the knowledge, attitude, and misconceptions regarding HIV/AIDS among university students in Pakistan. The objective is to gain insights into the effectiveness of educational interventions and their impact on the fight against HIV/AIDS. Study Design: A comprehensive literature search Place and Duration of Study: The review was conducted at SMBB Medical University Larkana Pakistan from March 2023 to April 2023. Materials and Methods: A narrative review of existing studies is performed to gather a comprehensive understanding of the knowledge, attitudes, and misconceptions related to HIV/AIDS among university students in Pakistan. Various electronic databases are searched to identify peer-reviewed articles, reports, and studies that investigate this topic. The selected studies are critically analyzed to extract relevant data and findings. Results: The review revealed that some studies demonstrate a lack of accurate understanding and misconceptions about the modes of transmission and prevention of the disease. However, educational interventions appear to have a positive influence on students' awareness and attitudes. Medical education, in particular, has shown promise in enhancing knowledge and altering attitudes among medical students and healthcare professionals. Conclusion: The findings underscore the significance of educational interventions in enhancing awareness and knowledge about HIV/AIDS among university students in Pakistan. By addressing misconceptions and promoting accurate information, these interventions can contribute to the prevention and control of the disease.